Primary torsion of the greater omentum - Alif Gul, Yunus Gul; Jabbar, Mohd Faisal; Moissinac, Kevin (ARSMB-KVBMG, 2001)
Primary or idiopathic greater omental torsion remains a rare cause of acute surgical abdomen in adults and children. The aetiology is as yet unknown and the treatment of choice, once diagnosis is established, is resection of the torted omentum. We report our experience with three such cases encountered over the last five years, two of which were diagnosed and subsequently managed laparoscopically. The performance of diagnostic laparoscopy for acute abdominal pain of an undetermined origin may lead to an increased detection of this condition and subsequent therapeutic intervention.